Dysfunction of neutrophils in patients with peptic ulcers, complicated with bleeding. - Sulayeva, O. N. (Морфологія / Morphologia / Morfologìâ, 2011)
To analyze a role of leukocytes dysfunction in the pathogenesis of ulcer bleeding the oxygen dependent metabolism, phagocytic activity and cytochemical indices of neutrophils were estimated in 100 patients with gatric and duodenal ulcers bleeding with effective hemostasis (group 1, n = 77) and rebleeding (group 2, n = 23). It was shown that peptic ulcer bleeding in patients of group 1 was associated with moderate increase of spontaneous production of active oxygen radicals, restriction of induced NADPH oxidase activity, decrease of acid phosphatase and myeloperoxidase activity but enhancement of phagocytic index. Sharp increase of spontaneous NBT-reaction with lost of oxidize functional reserve in neutrophils with significant inhibition of ability to phagocytosis and decreased of lysosomal enzymes activity were risk factors for rebleeding in patients of group 2.